Multi-purpose cash transfers and health among vulnerable Syrian refugees in Jordan: A prospective cohort study - Emily Lyles; Stephen Chua; Yasmeen Barham; Dina Jardenah; Antonio Trujillo; Paul Spiegel; Ann Burton; Shannon Doocy (Public Library of Science (PLoS), 2022)
Cash assistance has rapidly expanded in the Syrian refugee response in Jordan and global humanitarian programming, yet little is known about the effect of multipurpose cash transfers (MPC) on health in humanitarian contexts. A prospective cohort study was conducted from May 2018 through July 2019 to evaluate the effectiveness of MPC in improving access to healthcare and health expenditures by Syrian refugees in Jordan. Households receiving MPCs (US$113-219 monthly) were compared to control households not receiving MPCs using difference-in-difference analyses. Overall health care-seeking was consistently high (>85%). Care-seeking for child illness improved among MPCs but declined among controls with a significant adjusted difference in change of 11.1% (P<0.05). In both groups, child outpatient visits significantly increased while emergency room visits decreased. Changes in care-seeking and medication access for adult acute illness were similar between groups; however, hospital admissions decreased among MPCs, yet increased among controls (-8.3% significant difference in change; P<0.05). There were no significant differences in change in chronic illness care utilization. Health expenditures were higher among MPCs at baseline and endline; the only significant difference in health expenditure measures' changes between groups was in borrowing money to pay for health costs, which decreased among MPCs and increased among controls with an adjusted difference in change of -10.3% (P<0.05). The impacts of MPC on health were varied and significant differences were observed for few outcomes. MPC significantly improved care-seeking for child illness, reduced hospitalizations for adult acute illness, and lowered rates of borrowing to pay for health expenditures. No significant improvements in chronic health condition indicators or shifts in sector of care-seeking were associated with MPC. While MPC should not be considered as a stand-alone health intervention, findings may be positive for humanitarian response financing given the potential for investment in MPC to translate to health sector response savings.